Development and quality of ryegrass in an understorey of angico-vermelho in a silvopastoral system - Pilau, Janine; Elli, Elvis Felipe; Nardino, Maicon; Korcelski, Cleiton; Schmidt, Denise; Caron, Braulio Otomar (Comunicata Scientiae, 2015)
The aim of this study was to evaluate the development and quality of ryegrass in an understorey of angico-vermelho in a silvopastoral system. The experimental design was a complete randomized block, with a 2x6 factorial, being two systems of production (full sunlight and silvopastoral) and six times of harvest (15, 30, 45, 60, 75 and 90 days after ryegrass emergence), with three replications. The interception of the photosynthetically active solar radiation, average air temperature, dry matter, leaf area and protein content were evaluated. According to the analysis of variance, the interaction between production system and time of harvest resulted in significant differences for dry matter and the protein content and leaf area resulted in differences only according to the harvest time. The development of ryegrass is influenced by shading, when grown in this study conditions. The shade provided by angico-vermelho reduces the amount of ryegrass dry matter of ryegrass, but this reduction does not limit the use of the specie to compose a silvopastoral system. The total protein content and leaf area of ryegrass are not influenced by the light restriction.